1996
DOI: 10.1071/ah960104
|View full text |Cite
|
Sign up to set email alerts
|

Human resource management in hospitals: A contested arena for jurisdiction

Abstract: During the past 10 years, financial pressures on health service providers have led to a quest for more efficient service delivery and many consequential changes to the organisation and utilisation of staff. This study investigated the organisational responses to such pressures by four major South Australian hospitals and the level of involvement of hospital human resource staff in the staffing issues associated with strategic planning. With one exception, there was little contribution from qualified human reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…They also noted that there often existed contested ownership within the senior management structures with some hospital managers not willing to allow a strategic role for the HRM department. In the Australian part of the study Patrickson and Maddern (1996) found little evidence of strategic HRM taking place. Instead they found that hospital HR departments largely carried out a regulatory "personnel" function.…”
Section: Introductionmentioning
confidence: 86%
“…They also noted that there often existed contested ownership within the senior management structures with some hospital managers not willing to allow a strategic role for the HRM department. In the Australian part of the study Patrickson and Maddern (1996) found little evidence of strategic HRM taking place. Instead they found that hospital HR departments largely carried out a regulatory "personnel" function.…”
Section: Introductionmentioning
confidence: 86%
“…Previous studies have identified nursing as a stressful occupation (Schroeder & Worrall-Carter 2002;Stordeur, D'hoore & Vandenberghe 2001;Healy & McKay 1999). Among the unique sources of stress in nursing are: high work overload (largely due to difficulties in the recruitment and retention of nurses); stress derived from shift work and associated work/family-balance issues; role conflict associated with the dual responsibilities of administration and patient care; inadequate resources; and the perceived status of nurses as second-class citizens in health care organisations (Fitzgerald 2002;Stordeur, D'hoore & Vandenberghe 2001;Santamaria 2000;Patrickson & Maddern 1996). The Nurse Recruitment and Retention Committee Report (Victorian Government Depart-ment of Human Services 2001) concluded that nursing is increasingly becoming a physically and mentally exhausting occupation and nurses are no longer prepared to work under the resultant stress.…”
Section: Context Of the Researchmentioning
confidence: 99%
“…However, the majority of the literature has tended to focus on individual aspects of workplace change only, such as the rise and rationales for part-time work. The attention of Australian researchers has primarily been focused on the increasing use of private sector practices in the public hospital sector (eg, Patrickson and Maddern 1996;Stanton 1999).…”
Section: Introductionmentioning
confidence: 99%